A Platform for the Recommendation of Points of Interest in Brazilian Cities - Architecture and Case Study - Domingues, Marcos Aurélio; Santos, Thais Emanuele; Hanada, Raíza; Cunha, Bruna C. R.; Rezende, Solange Oliveira; Pimentel, Maria da Graça Campos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2015: Proceedings of the 21st Brazilian Symposium on Multimedia and the Web, 2015)
The tourism sector in Brazil has grown considerably in recent years. Despite this growth, the sector still presents several problems such as the lack of information in Portuguese and in other languages for Brazilian and foreign tourists. The absence of information about tourist sites and ordinary services also affects individuals when settling in a new city, as it is the case when freshman students move to a new city to start their studies in a college or university. In this work, we propose an innovative vision of a context-aware platform for recommending points of interest in Brazilian cities, designed with mechanisms for collecting data from the web, for extracting points of interest and background information, and for learning context-aware recommendation models. The platform is accessed by a mobile application. To validate our proposal, we ran a case study where freshman students used the platform during their first months in a new city.